Non-pharmacological methods of controlling nausea and vomiting during pregnancy in Iran: A narrative review study - Hashem Jarineshin; Seyed Ebrahim Sadeghi; Mehrdad Malekshoar; Mohammad Sadegh Sanie Jahromi; Fatemeh Rahmanian; Naser Hatami; Navid Kalani (Mashhad University of Medical Sciences, 2022)
Introduction: Nausea and vomiting are common complaints of women in the first half of pregnancy. Several pharmacological and non-pharmacological methods have been suggested to prevent nausea and vomiting. Since pharmacological treatments are associated with side effects, this study was performed with aim to investigate non-pharmacological methods of controlling nausea and vomiting during pregnancy in Iran.Methods: In this narrative or narrative review study, all the articles published in domestic Persian language journals were searched using the databases of SID, Magiran and Google Scholar search engines, and the use of Persian keywords of non-pharmacological methods, nausea, vomiting and pregnancy and a combination of these keywords between 2001 and 2021. In this study, only original and clinical trial studies were reviewed.Results: Among the searched 679 articles, 28 related articles which had all the information in the designed checklist were included in the study. Based on the results, several non-pharmacological methods including use of acupressure, Benson relaxation training, progressive muscle relaxation, Ottawa Nutrition Guide, Solar Soil Reflexology, Lemon Aromatherapy, Psychological counseling with a couple therapy approach, Family-centered Counseling, Telephone Support, and herbal remedies such as ginger, chamomile and cardamom were effective in treating pregnancy nausea and vomiting.Conclusion: The present study showed good evidence for the effectiveness and safety of all methods used in the studies. It seems that all non-pharmacological methods of nausea and vomiting such as acupressure can be used as very easy methods in the treatment of pregnant women; however, the present study was not able to evaluate the preference of the proposed methods that health care providers can choose from the methods supported by previous evidence from clinical trial studies according to the available facilities and patient preferences.